Enantioselective Michael Addition/Iminium Ion Cyclization Cascades of Tryptamine-Derived Ureas - Aillaud, Isabelle (American Chemical Society, 2013)
[Image: see text] A Michael addition/iminium ion cyclization cascade of enones with tryptamine-derived ureas under BINOL phosphoric acid (BPA) catalysis is reported. The cascade reaction tolerates a wide variety of easily synthesized tryptamine-derived ureas, including those bearing substituents on the distal nitrogen atom of the urea moiety, affording polyheterocyclic products in good yields and good to excellent enantioselectivities.